Penerapan Lembar Kerja Eksperimen Untuk Melatih Keterampilan Proses Sains Siswa SMA - Hikmawati Hikmawati; Kusmiyati Kusmiyati; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
Limited trial studies have been carried out on the application of Experimental Worksheets to train High School Student Science Process Skills (SPS). The limited trial subjects of the application of worksheets were students of class XI IPA-1 at SMAN 1 Kediri in the 2017/2018 Academic Year with a total of 21 people. The number of worksheets tested in physics learning material Temperature, Heat, and Heat Transfer are a number of 6 pieces consisting of worksheets for experiments Putting test marks on Thermometers, Substance Expansion, Change in Objects, Black Principle, Heat Transfer, and Heat Equation. Worksheets in this study aimed to trains students to improve the ability to formulate problems, make hypotheses, conduct experiments, and interpret information. In implementing these worksheets, the teacher uses the experimental method in learning activities with 4 meetings. The average SPS score obtained by students for each worksheet is 80 with good criteria. Thus, worksheets can be an alternative for physics teachers in training SPS students in high school